TARBIYACHINING KASBIY KOMPETENTLIGINI SHAKLLANTIRISH - Quchqorova, N.M.; Matchanova, N. (SCIENCE and SOCIETY, 2022)
This article discusses the concept of “competence”, the circumstances that define professional competence, and the importance of self-improvement and self-development in gaining professional competence.